The Partition Dimension on the Grid Graph (Jurnal Matematika, Statistika dan Komputasi, 2023)
Graph G is a discrete set pair with the notation V(G)   with its element called a vertex and the set of different and unordered pairs with the notation E(G)   where the element is called edge. One type of graph Gm,n is a grid graph that is notated  is a graph of the result of the operation between two path graphs (Pm*Pn).  The set of partition∏ ={S1,S2,…,Sk} of V(G) is called a resolving partition if its representation for each vertex on graph G is different. The cardinality of the minimum resolving partition of graph G is the partition dimension of the graph G denoted pd(G). This paper discusses the dimension of the grid graph partition Gm,n  with the result pd(Gm,n) = 3 for m,n>=2 with n even value.
Keywords: grid graph; partition dimensions; resolving partition; partition set